(untitled) (Global Journal of Management and Business Research, 2015)
This article research the possibility of boosting economic growth from an outside source of funding as official development assistance, the example given is that of Cameroon. The purpose of this paper is to check the effects of ODA on economic growth in Cameroon. The data used come mainly from the World Bank, in "the book of world development indicators" on the CD -ROM (WDI 2014). Working for the period 1980-2013, the analysis was made with an error correction model. The endogenous variable is the real income growth rate per capita. Estimates made from the method of Johansen (1988), it emerges that the ODA has no effect on economic growth in the public Cameroun. Official development assistance, in its form of technology transfer, combined with good governance, could have a significant effect on economic growth.